2016
DOI: 10.1103/physreve.94.062902
|View full text |Cite
|
Sign up to set email alerts
|

Nonvibrating granular model for a glass-forming liquid: Equilibration and aging

Abstract: We studied experimentally a model of a glass-forming liquid on the basis of a nonvibrating magnetic granular system under an unsteady magnetic field. A sudden quenching was produced that drove the system from a liquid state to a different final state with lower temperature; the latter could be a liquid state or a solid state. We determined the mean-squared displacement in temporal windows to obtain the dynamic evolution of the system, and we determined the radial distribution function to obtain its structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…The effective temperature can also be determined from the Maxwell-Boltzmann velocity distribution. For a wide range of temperatures, we observed that T E is proportional to B o 16 . In this work we used B o to characterize the energy of the particles.…”
Section: Methodsmentioning
confidence: 82%
See 3 more Smart Citations
“…The effective temperature can also be determined from the Maxwell-Boltzmann velocity distribution. For a wide range of temperatures, we observed that T E is proportional to B o 16 . In this work we used B o to characterize the energy of the particles.…”
Section: Methodsmentioning
confidence: 82%
“…We studied two cases of the constant magnetic field, B c = 0 G and B c = 36 G, in both cases ν = 9.25 Hz, and B o takes values from 0 to 63 G. The case with B c = 36 G was already considered in Refs. 16,19,20 . The two-dimensional packing fraction (particle concentration) is defined by φ s = Nπσ 2…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The system is open at the top but gravitation maintains the system two dimensional. Instead of mechanically vibrating the system or injecting an upflow of gas as in other works 18 , 20 25 , here we provide kinetic energy to the particles by applying a vertical time dependent sinusoidal magnetic field 26 . The interaction of the varying magnetic field with induced magnetic dipole on the particles, produces a time dependent net force on each particle keeping them in motion.…”
Section: Resultsmentioning
confidence: 99%